Nanofluid flow between disks in the presence of thermal radiation and heat source: stability analysis (Persatuan Sains Matematik Malaysia, 2023)
The internal flow between disks is used in various applications, including rotating machinery, aircleaning machines, food processing technology, and gas turbine rotors. The present study analyses the nanofluid flow between a non-permeable, stationary disk and a permeable, rotating, shrinking disk. Radiation and heat generation effects are included in the proposed governing partial differential equations and boundary conditions. Then, non-linear ordinary differential equations and boundary conditions are derived through the similarity transformations for numerical computation in MATLAB. Dual solutions from the computation prompted a stability analysis; only the first solution is stable. Enhancing thermal radiation and heat generation parameters reduces and increases the temperature profile throughout the internal flow. Meanwhile, increasing the shrinking parameter and Reynolds number reduces the radial and tangential velocities in some regions close to the stationary, nonpermeable disk.